The role of knowledge-based psychological climates in human resource management systems. Issue 5 (20th June 2016) - Meyer, David; Dunphy, Steve
Abstract : Purpose: – Responding to Colbert's (2004) call for research examining the complexity of work systems' effect on performance, and following Meyer and Dunphy's (2014, 2015) work determining the general manner by which the complex mechanism of strategy choice and its implementation effect corporate performance, the purpose of this paper is to specify and test a model of the effects of workplace factors affecting employee responses to the demand for increased knowledge in using technology. Design/methodology/approach: – Drawing on the literature on the resource-based view of strategy and the knowledge-based (KB) view of human resource management system implementation, theory is developed, and hypotheses are generated, regarding employee attitudes toward skill development, technology, employment security, and feedback and their impact on competence and impact. Meaningfulness, self-determination, work conditions, and intensity are controlled for. Data from a sample of 888 employees, 24 managers, and corporate executives across eight Detroit-area automotive supplier firms are used to test the model using structural equation modeling. Findings: – Individual psychological states of competence and impact are positively and strongly associated with KB psychological climates that foster and condition positive beliefs about the importance of learning new skills and about the effects of the diffusion of new technologies on employees. Research limitations/implications: – The complexity of the interactions of management implementation of workplace practices on employee performance still needs more sorting out. Only unionized employers pursuing high-involvement work systems were studied. Other types of employers would have very different workplace climates. Practical implications: – Only unionized employers pursuing high-involvement work systems were studied. Other types of employers would have very different workplace climates. Social implications: – In order to have employees be receptive to changing technology and the resulting, increased demands for knowledge and skill, employers have to provide long-term employment security. Originality/value: – The results provide the specific manner by which employers can increase employee receptiveness to increase workplace knowledge and training to have more impact on their performance.